"Komunia w Duchu " : małżeństwo a Eucharystia w świetle norm kanonów 1065 § 2 i 1119 KPK - Pastwa, Andrzej (Ius Matrimoniale, 2012)
“The Eucharist is the very source of Christian marriage.” This crucial sentence from the “Familiaris Consortio” apostolic exhortation(no. 57), in which John Paul II contained the truth about the immanent nature of relations binding the mentioned-above sacraments, constitutes a kind of invitation to a deepened understanding of the “de sacramento matrimonii” doctrine of the Second Vatican Council. In this context, worth emphasizing is the significance of canon 1065, paragraph 2 and 1119 regulations in John Paul II’s Code of 1983. The first of those regulations combines a fruitful contracting of a sacramental relationship by Catholic nupturients with receiving the Eucharist while the other one refers to the very ceremony of the “Seventh Sacrament”, indirectly communicating the meaning the Church attaches to the liturgical form of the marriage contract. However, do the mentioned-above code norms really play their function well? This article is an attempt at answering the question on the basis of clearly defined epistemological-methodological assumptions, with the key one which has the following meaning: we must assign the rank of paradigm to the sacramental “triad”: Baptism, Matrimony and Eucharist. As I have tried to show in my work, this study perspective is particularly helpful in drawing conclusions for the legal-canonical field, namely for detecting shortcomings of canon norms: 1065, paragraph 2 and 1119 of the Code of Canon Law.